ARTICULAR DILUTIONINIG ALTERATION IN KNEE JOINT OSTEOARTHROSIS - Maxmudov Boburbek Erkinovich (The Conference Hub, 2025)
With osteoarthrosis, the amount of hyaluronate in the knee decreases, so the synovial fluid loses its viscosity. Mechanical stress on the cartilages of the joint increases, so their wear accelerates. This problem can be solved by injecting prosthetic synovial fluid (hyaluronic acid). In this article highlights of articular dilutioninig alteration in knee joint osteoarthrosis.
Keywords: Knee joint, osteoarthrosis, articular dilutioninig, articular sac (synovitis), diagnostics and treatment.